Eriophyes pouteriae sp. nov., a New Mite Species Infesting Pouteria sapota † - De Giosa, Marcello; de Lillo, Enrico; Tassi, Aline D.; Revynthi, Alexandra M.; de Andrade, Daniel J. [UNESP]; Ochoa, Ronald; Yang, Xiangbing; Carrillo, Daniel (MDPI, 2024)
Abnormal leaf growth, including stunted leaves, outward curling, leaf yellowing, and diminishing overall tree vigor of Pouteria sapota [(Jacq.) H.E. Moore et Stearn] (Sapotaceae) was observed in multiple locations in Southern Florida and one location in Brazil. In search for possible causal agents of these damages, a new mite species of the family Eriophyidae was found persistently infesting closed leaf buds of P. sapota. It was morphologically described and named Eriophyes pouteriae sp. nov.; DNA sequences of usual regions were also obtained. This is the first eriophyoid mite associated with P. sapota.
Keywords: bud mites Eriophyoidea; Eriophyidae; Eriophyinae; mamey sapote; molecular markers; morphological description